Perancangan Antena MIMO 8x8 Frekuensi Kerja 3,5 GHz Untuk Teknologi 5G - Nasrul, Nasrul; Nindika, Aprilia; Yustini, Yustini; Septima, Uzma (Elektron : Jurnal Ilmiah, 2023)
The 8×8 MIMO antenna is designed and simulated using CST Studio Suite 2019 software, which generates a visualization using MATLAB software. After optimization, the measurement and simulation of the return loss parameters at a frequency of 3,5 GHz yielded results of -11,85 dB and -31,57 dB respectively. In addition, there are several other frequency ranges with values below -10 dB, such as between 3,047 GHz and 3,243 GHz, 3,438 GHz and 3,925 GHz, and 4,575 GHz and 5,095 GHz. The measured VSWR is 1,668, while the simulation results show a VSWR value of 1,054. In addition, the Mutual Coupling simulation result is -13,16, while the Mutual Coupling measurement is -28,53, with ECC values of 0,0005 and 0,0002, respectively.